Implementasi Metode Sariswara Karya Ki Hadjar Dewantara pada Sekolah Dasar di Kecamatan Mergangsan Yogyakarta - Sri Ratna Saktimulya; Akhmad Nugroho; R. Bima Slamet Raharja (Faculty of Cultural Sciences, 2019)
Today's elementary school students assume that the Javanese language is a foreign language. Tis situation had been predicted by Ki Hadjar Dewantara, therefore in 1930 he created Sariswara method as a means of facilitating the learning of Javanese language and literature. Tis community service aims in sharing the concept of Ki Hadjar Dewantara’s Sariswara method in improving Javanese language profciency and enriching knowledges of Javanese literatures through songs and dances in the targeted community. Tis community services involved teacher representatives, students, and parents of students of 12 Elementary Schools in Mergangsan Sub-district. Te provision of the materials and training is expected to foster a sense of pride in their own culture, so that they will be motivated to preserve and develop it, afterward. Eventually, it is hoped that a community that preserves the Sariswara method will emerge. Strengthening the sense of love for Javanese language and literature through tembang dolanan (songs of singing games) and dance movements stimulates students’ intelligence.================================================================== Murid sekolah dasar masa kini menganggap bahasa Jawa sebagai bahasa asing. Keadaan seperti ini telah diprediksi oleh Ki Hadjar Dewantara sehingga pada 1930 diciptakan Metode Sariswara sebagai sarana mempermudah pembelajaran bahasa dan sastra Jawa. Tujuan pengabdian kepada masyarakat ini adalah menyebarkan konsep Ki Hadjar Dewantara tentang Metode Sariswara melalui pengayaan materi bahasa, sastra, tembang, dan gerak tari. Melalui pemberian materi dan pelatihan (praktik) kepada perwakilan guru, siswa, dan orang tua siswa di 12 sekolah dasar se-Kecamatan Mergangsan ini diharapkan dapat menumbuhkan rasa bangga terhadap budaya bangsa sendiri dan mengembangkannya, yang pada akhirnya akan terbentuk komunitas pecinta Metode Sariswara. Penguatan rasa cinta terhadap bahasa dan sastra Jawa dengan sarana tembang dolanan dan gerak tarinya menstimulasi kecerdasan siswa.